Technique analysis in junior slalom ski racing through pressure distribution measurements - Raschner, C.; Graupp, M.; Niederkofler, A.; Mildner, E.; Platzer, H.-P.; Lembert, S.; Patterson, C. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The margin of technical skill differences between Austrian high performance junior ski racers is getting smaller and smaller. Precise analysis to allow even minor technique changes in this age group will lead to improved performance. Dynamic force measurements coupled with kinematics and electromyography analysis in ski racing have been made predominantly with adults. To our knowledge, no published work has analyzed the pressure distribution in Slalom (SL) with 11 to 14 year old high level junior ski racers.